Achieving Sustainable Development Goals (SDGs) in The Village Through Good Governance: Inclusive Perspective - Anggraini, Nita; Kumalasari, Ana; Junadi, Junadi; Rahimjon, Dilbarova Malika (Publik : (Jurnal Ilmu Administrasi), 2025)
This research aims to analyze application of good governance pronciples in supporting the inclusion of people with disabilities in the villages of Bojonegoro Regency to acvhieve the Sustainable Development Goals (SDGs). Even though various social assistance programs have been distributed, there are still gaps in accessibility for people with disabilities in vilages, which indicates a lack of inclusive governance. This research uses a qualitative Approach with a case study method in several villages in Bojonegoro, Which were selected based on the relevance and diversity of regional characteristic. Data wa collected through in depth interviews. Research informants included village heads, village offocials, and people with disabilities. The research results show that the application of good governance principles such as transparency, accountability, and participation in the distribution of social assistance is not optimal, so access for people with disabilities remains low. This research provides is not optimal, so acces for people with disabilities remains low. This research provides practical contributitions that support regional policies to strengthen inclusive governance that supports the achievement of SDGs at the local level.